Development and Assessment of a Video-Based Intervention to Improve Rhinoplasty Informed Consent - Hakimi, Amir Aaron; Standiford, Lauren; Chang, Edward; Wong, Brian Jet-Fei (Facial Plastic Surgery, 2021)
There has been a growing interest in improving the informed consent process to ensure patients truly understand the benefits, risks, and alternatives of their procedures. Herein, we sought to describe the production of an educational video to supplement the traditional rhinoplasty informed consent process. Additionally, we evaluate satisfaction and risk recall among prospective rhinoplasty patients who participated in the video-assisted informed consent process. One author attended 30 rhinoplasty consultations where informed consent was performed and generated 65 questions related to the benefits, risks, alternatives, and general knowledge of rhinoplasty operations. A video of the senior author answering these questions was filmed and edited to 25 minutes. Prospective rhinoplasty patients watched the video before their initial consultation and were asked to complete two surveys assessing their satisfaction with the video-assisted process as well as their ability to recall risks discussed in the video. Understandability and actionability of the video was assessed by three independent reviewers using the Patient Education Materials Assessment Tool. Postvideo surveys were completed by 40 patients. Patients strongly agreed that the video informed them about rhinoplasty risks and benefits (4.90/5.00), effectively answered their questions and/or concerns (4.78/5.00), and provided adequate information before surgery (4.85/5.00). Participants strongly recommended that all prospective patients watch the video prior to surgery (4.97/5.00). Participants on average correctly answered 4.00 ± 0.877 out of five risk recall questions. There was no statistically significant difference in risk recall performance between college graduates (4.19 ± 0.602) and those who did not graduate college (3.79 ± 1.08), p = 0.076. No significant correlation was found between patient age and recall performance (r = –0.011), p = 0.943. The overall mean understandability and actionability scores for the video were 100%. Video-assisted informed consent for rhinoplasty may enhance and overcome limitations to the traditional verbal consent process by ensuring comprehensive, standardized, and readily understandable information.
Keywords: rhinoplasty; informed consent; quality improvement; patient education; video